Fine-Mapping of the Major Histocompatibility Complex Region Linked to Leprosy in Northern China - Zhang, Ruixue; Cao, Lu; Chen, Weiwei; Ge, Huiyao; Hu, Xia; Li, Zhuo; Wang, Yirui; Fan, Wencheng; Yong, Liang; Yu, Yafen; Mao, Yiwen; Zhen, Qi; et al. (Frontiers in Genetics, 2021)
Background: Leprosy is a chronic infectious skin and neurological disease, and genetic background is considered to be one of the major factors of risk. The major histocompatibility complex (MHC) region not only affects susceptibility to leprosy but also its development and outcome. Given the complex traits of the MHC region, variants and the potential mechanism by which HLA influences leprosy development need to be further explored. Methods: We extracted previous genome-wide association study data for the Northern Han Chinese population to perform HLA fine-mapping. Using the 1000 Genome Project Phase 3 dataset as the reference panel, single-nucleotide polymorphisms (SNP), insertion and deletion (INDEL) and copy number variant (CNV) imputation were carried out. HLA classical alleles and amino acids in the MHC region were imputed using the HAN-MHC database. Further stepwise regression analysis was conducted to analyze independent signals of variants related to leprosy. Results: We identified four independent variants: esv3608598, rs7754498, rs3130781 and rs144388449. Among them, esv3608598 is a CNV and the first HLA CNV associated with leprosy risk. SNP annotation using RegulomeDB, HaploReg, and rVarBase showed that three SNPs are likely to affect the pathogenesis of leprosy. Conclusions: In summary, this is the first study to assess the association between HLA CNV and leprosy susceptibility in a Northern Han Chinese population. By fine mapping of the MHC region in this population, our findings provide evidence for the contribution of HLA to leprosy susceptibility.